2005
DOI: 10.1002/chin.200507037
|View full text |Cite
|
Sign up to set email alerts
|

Scandium—Bipyridine‐Catalyzed Enantioselective Addition of Alcohols and Amines to meso‐Epoxides.

Abstract: Ring opening reactions O 0132Scandium-Bipyridine-Catalyzed Enantioselective Addition of Alcohols and Amines to meso-Epoxides. -The first catalytic enantioselective addition of aliphatic alcohols (II) to meso-epoxides (I) is presented using a Sc(O-Tf)3-chiral bipyridine complex as catalyst. The reaction affords mono-protected anti-diols (III) in high yields and selectivities for aryl-substituted epoxides. The novel catalytic complex is successfully applied to the enantioselective addition of amines (IV) to meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…As the amount of nucleophile was reduced to 0.4 equiv, there was a slight improvement in the ee of the product but with significantly lower yield ( Table 1, entries 15 and 16). On increasing the amount of nucleophile (0.6-0.75 equiv) there was a steady decrease in the ee of product anti-b-aminoalcohol with concomitant increase in the ee of trans-stilbene oxide (83-96%; Table 1, entries [17][18][19][20]. Hence, the kinetic resolution reaction can be optimized depending upon which product (epoxide or aminoalcohol) is required in higher chiral purity by simply adjusting the amount of nucleophile (aniline) used.…”
Section: Recycling Experimentsmentioning
confidence: 95%
See 1 more Smart Citation
“…As the amount of nucleophile was reduced to 0.4 equiv, there was a slight improvement in the ee of the product but with significantly lower yield ( Table 1, entries 15 and 16). On increasing the amount of nucleophile (0.6-0.75 equiv) there was a steady decrease in the ee of product anti-b-aminoalcohol with concomitant increase in the ee of trans-stilbene oxide (83-96%; Table 1, entries [17][18][19][20]. Hence, the kinetic resolution reaction can be optimized depending upon which product (epoxide or aminoalcohol) is required in higher chiral purity by simply adjusting the amount of nucleophile (aniline) used.…”
Section: Recycling Experimentsmentioning
confidence: 95%
“…trans-stilbene oxide does not commence ( Table 2, entries 11 and 12). AKR of trans-b-methyl styrene oxide with aniline gave exclusively anti-b-aminoalcohol with moderate ee and yield (Table 2, entries [13][14][15][16][17][18]. Based on the optical rotation studies for the products 7b-7c, their absolute configuration was shown to be 1S,2R.…”
mentioning
confidence: 95%
“…All products were characterized by appropriate spectroscopic techniques, microanalysis, LCMS, and optical rotation, which were found to be in consonance with the reported values. 7,8,19,20 Recycling of the Catalyst…”
Section: Typical Experimental Procedures For Ringmentioning
confidence: 99%
“…In recent years, chiral amino alcohols have found a distinct role as chiral ligands for various metal-catalyzed asymmetric organic transformations. [1][2][3][4][5][6][7][8] To synthesize chiral b-amino alcohols, several strategies, namely, aminohydroxylation of olefins, 9,10 addition of a-hydroxy ketones to imines, [11][12][13] aminolytic kinetic resolution of racemic terminal/trans aromatic epoxides, [14][15][16][17][18] and asymmetric ring opening (ARO) of meso-epoxides, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have been reported in the literature. Among these, metal-catalyzed ARO of meso-epoxides with amines is one of the most elegant, atom efficient, and straightforward strategies for the synthesis of chiral b-amino alcohols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation